Scope and Focus of the 2017 Review of the Standards and Codes Initiative. (Policy Papers; Policy Paper ;, 2017)
The standards and codes (S and C) initiative was launched in 1999 as part of efforts to strengthen the international financial architecture. The initiative aims at promoting international best practices to improve economic and financial resilience through three intermediate objectives: assist countries in strengthening their economic institutions, inform World Bank and IMF work, and inform market participants. The four previous reviews confirmed a fairly high appreciation of the overall initiative. However, the related comprehensive surveys and engagement with stakeholders raised questions about the initiative's link to surveillance and capacity-building efforts, as well traction with market participants and policy makers. This paper is designed to engage with the Executive Board on the overall scope and focus of the 2017 review of the S and C initiative. The continuous evolution of the S and C and work under the initiative has accelerated in several policy areas since the financial crisis. Several areas of the S and C have been substantially reformed (fiscal and financial codes) or updated (corporate governance and insolvency and creditor rights) to reflect evolving international best practices, while potential changes in some others are still under consideration (data and monetary and financial policy transparency). The overall level of assessment activity under the initiative has fallen moderately, with a sharp drop in formal Reports on the Observance of Standards and Codes (ROSCs) partly offset by an increase in other types of S and C based outputs, such as evaluations. Since the 2011 review, most of the changes to individual S and C policy areas under the initiative have involved direct Board engagement, and have aimed at improving operational effectiveness to promote international best practice in the specific area. The review is an opportunity to discuss how the initiative may be adapted to maintain its relevance, and to capitalize on its achievements. The review will look at changes to the S and C and their applications-across and within the individual policy areas-and make recommendations on the overall initiative. This informal session to engage provides a factual update of the S and C initiative since the last review in 2011, and proposes a strategic approach to address gaps and weaknesses, coordinate reviews of individual policy areas and the overall initiative, and continue to strengthen the relationship with external standard setters and assessors.